Pengaruh Keputusan Investasi, Kebijakan Dividen, Keputusan Pendanaan, Profitabilitas dan Likuiditas Terhadap Nilai Perusahaan - Achmad Nurcholik; Augustina Kurniasih (Warta Pendidikan | e-Journal, 2021)
This study aims to influence investment decisions, dividend policies, funding decisions, profitability and liquidity on the value of the company of the consumer goods sector listed on the Indonesia Stock Exchange during the 2012-2017 observation period. The research sample consisted of 36 companies determined by purposive sampling. The study uses secondary data from annual financial reports issued by companies in the consumer good sector. The research method used is descriptive statistics and panel data regression using Fixed Effect Model (REM). The results showed that investment decisions, dividend and liquidity policies did not affect the Price Book Value while funding and profitability decisions had a significant positive effect on the Price Book Value. The implication in this study is that companies need to pay attention to funding decisions and profitability because both are proven to have a positive effect on firm value.